Comparing parental acceptance: the rejection levels and peer relationships of Turkish preschool children - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
The aim of this research was to compare the parental acceptance-rejection levels and peer relationships of 5-6 year old preschool children. The sample used in this research consisted of 150 children and their parents who were living in Denizli, Turkey. The results indicated that the mother's acceptance-rejection level had a significant predictive effect on the victimisation, aggression, pro-social behaviour, exclusion and hyperactivity of 5-6 year old children. The father's acceptance-rejection level did not have a significant predictive effect with regard to the pro-social behaviours, aggression, asocial behaviours, exclusion, fear-anxiety, hyperactivity-distractibility and victimisation of 5-6 year old children. In addition, when both the mother and father's acceptance-rejection levels were taken into account together, they had a significant predictive effect with regard to aggression, exclusion, hyperactivity-distractibility and victimisation. (c) 2011 Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: parental acceptance-rejection; peer relationships; preschool children; MENTAL-HEALTH; ADJUSTMENT; CHILDHOOD; AGGRESSION; FAMILY